La imprenta en Toledo: estado de la cuestión. - Reyes Gómez, Fermín de los (Revista General de Información y Documentación, 2000)
A brief analysis of works conceming printing in Toledo since its begin nings with Cribóbal Pérez Pastor in 1887. A project for making a bibliography of works from the Toledo presses from the XV to the XVIII century is also des cribed.
Keywords: Printing Toledo Bibliography